Risk factors for mediastinitis in the post-operative period of heart surgery / fatores de riscos para mediastinite no pós-operatório de cirurgia cardíaca - Debora Ferreira da Cruz; Elbanir Rosangela Ferreira de Sousa; Claudia Elizabeth de Almeida (Universidade Federal do Estado do Rio de Janeiro, 2020)
Objectives: The study's main purpose has been to identify both pre and postoperative risk factors related to the development of mediastinitis among patients who underwent cardiac surgery at a hospital from the Rio de Janeiro city. Furthermore, to characterize the study population and to analyze the relationship between risk factors and the incidence of mediastinitis in patients who underwent cardiac surgery. Methods: It is a descriptive and retrospective study with a quantitative approach, where there were identified the risk factors related to the development of mediastinitis in patients who underwent cardiac surgery at a university hospital from the Rio de Janeiro State. Results: There were obtained a total of 192 patients, mostly males, within the age group from 50 to 69 years old and overweight. Diabetes mellitus and smoking were the most frequent comorbidities, and coronary artery bypass graft surgery was the most performed surgery, 4 patients had mediastinitis. Conclusion: The identification of such factors contributes to the elaboration of prevention strategies for mediastinitis, and the implementation of nursing care in both pre and postoperative periods of cardiac surgeries.